In situ characterization of trans-laminar fracture toughness using X-ray Computed Tomography. (October 2020) - Sun, Xiaoyang; Takeda, Shin-ichi; Wisnom, Michael R.; Xu, Xiaodong
Abstract: The change in the critical strain energy release rate as damage evolves, known as the R-curve, is of crucial importance to the understanding of fracture behaviour. The examination of damage evolution ahead of the crack tip in order to determine accurately the crack increment is key for the determination of the R-curve. Conventional in situ methods such as optical measurements only examine the specimen surfaces. X-ray Computed Tomography (CT) offers satisfactory image quality, but conventional CT scanning requires the removal of the specimens from the test machine. If no dye penetrant is used, the specimens can be re-loaded, but some important information will be missing such as the early load drops corresponding to damage initiation. If dye penetrant is used, the specimens can no longer be re-tested. In contrast, in situ CT scanning can capture the detailed damage states ply-by-ply while the specimen is loaded and diminish the need for multiple specimens. In situ characterization of trans-laminar fracture toughness of composites using CT has not been attempted in the past. It has been proven successful in this research, and shown that a partial R-curve can be constructed with a single Extended Single-Edge-notch Tension (ESET) specimen. Highlights: An R-curve for translaminar fracture exists in the Non-Crimp Fabric carbon/epoxy laminates. Crack increments are measured using in situ Computed Tomography (CT) scans. The quality of the current in situ CT scan images is as good as the previous conventional CT scans with dye penetrant. ASTM E1922 standard is only suitable to generate a partial R-curve.